2017
DOI: 10.1302/0301-620x.99b5.bjj-2016-1232.r1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for failure of the 36 mm metal-on-metal Pinnacle total hip arthroplasty system

Abstract: AimsTo determine ten-year failure rates following 36 mm metal-on-metal (MoM) Pinnacle total hip arthroplasty (THA), and identify predictors of failure.Patients and MethodsWe retrospectively assessed a single-centre cohort of 569 primary 36 mm MoM Pinnacle THAs (all Corail stems) followed up since 2012 according to Medicines and Healthcare Products Regulation Agency recommendations. All-cause failure rates (all-cause revision, and non-revised cross-sectional imaging failures) were calculated, with predictors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
(86 reference statements)
0
19
0
Order By: Relevance
“…[2][3][4] This has triggered regulatory alerts, device recalls and mandatory surveillance programs. The failure of these devices has led to many patients subsequently undergoing early revision.…”
Section: Cite This Article: Bone Joint J 2018;100-b:20-7mentioning
confidence: 99%
“…[2][3][4] This has triggered regulatory alerts, device recalls and mandatory surveillance programs. The failure of these devices has led to many patients subsequently undergoing early revision.…”
Section: Cite This Article: Bone Joint J 2018;100-b:20-7mentioning
confidence: 99%
“…3,[11][12][13] High revision rates have been reported for MoM THRs with Pinnacle cups (subsequently referred to as Pinnacles) in registries 3,11 and large single-centre studies. 12,[14][15][16][17] Two recent studies together involving over 1,000 primary 36 mm Pinnacles (8.4% of all such implants within the National Joint Registry (NJR)) both reported that hips implanted from 2006 onwards had a significantly increased risk of failure compared with those implanted before 2006. 12,17 Explant analysis also demonstrated that Pinnacles manufactured from 2006 onwards were increasingly likely to have lower clearance values than intended by the manufacturer.…”
Section: Introductionmentioning
confidence: 99%
“…12,[14][15][16][17] Two recent studies together involving over 1,000 primary 36 mm Pinnacles (8.4% of all such implants within the National Joint Registry (NJR)) both reported that hips implanted from 2006 onwards had a significantly increased risk of failure compared with those implanted before 2006. 12,17 Explant analysis also demonstrated that Pinnacles manufactured from 2006 onwards were increasingly likely to have lower clearance values than intended by the manufacturer. 12 It has been postulated that these previously unrecognised changes in the device manufacturing process may be responsible for the increased failure rates reported from 2006 onwards.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations